Participação de pequenos grupos neurais seletivamente ativados do córtex pré-límbico na reinstalação da autoadministração de etanol induzida pelo contexto - Palombo, Paola (Universidade Federal de São Carlos, 2017)
Context-induced reinstatement of drug seeking is an animal model for assessing the neural mechanisms underlying context-induced drug relapse, a major factor in human drug addiction. Neural activity in prelimbic cortex has been implicated in context-induced reinstatement drug seeking. Here, we report a new and feasible training procedure for context-induced reinstatement of alcohol seeking to explore the role of prelimbic cortex in context-induced relapse to alcohol seeking. Long-Evans rats were first given home-cage access to 10% ethanol. Using a saccharin fading technique, rats were first trained to self-administer 10% ethanol in one context. Next, lever pressing in the presence of the discrete cue was extinguished in a different context. Subsequently, context-induced reinstatement of drug seeking was assessed by re-exposing rats to the drug-associated or extinction context under extinction conditions. Re-exposure to the alcohol-associated context reinstated alcohol seeking and increased expression of the neural activity marker Fos in the prelimbic prefrontal cortex. The percentage of neural activation in this brain region was 3.4 % in extinction context and 7.7 % in drug associated context. Reversible inactivation of neural activity in prelimbic prefrontal cortex using GABA agonists muscimol and baclofen attenuated context-induced reinstatement. Based on previous findings of the literature that Fos-expressing neurons play a critical role in conditioned drug effects, we assessed whether context-induced reinstatement was associated with molecular alterations selectively induced within context-activated Fos-expressing neurons. We used fluorescence-activated cell sorting to isolate reinstatement-activated Fos-positive neurons from Fos-negative neurons in prelimbic cortex and used quantitative PCR to assess gene expression within these two populations of neurons. Context-induced reinstatement was associated with increased expression of the GABAα5 gene and decrease in the AMPA receptor subunit genes GluR1 and GluR2 in only Fos-positive neurons. Our results demonstrate an important role of prelimbic cortex in context-induced reinstatement of alcohol seeking and that this reinstatement is associated with unique gene alterations in Fos-expressing neurons.
Keywords: Autoadministração; Etanol; Extinção; Contexto; Recaída; Ratos; Self-administration; Alcohol; Extinction; Context; Drug relapse; Rats; CIENCIAS BIOLOGICAS::FISIOLOGIA